2018
DOI: 10.1177/1609406918813772
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Liming and Ole Talk as a Culturally Relevant Methodology for Researching With Caribbean People

Abstract: This article explores the necessity of developing a qualitative research methodology grounded in Caribbean peoples' worldviews and interactions. It presents the epistemology and ontology of liming and ole talk to show their natural employment in qualitative research settings. Liming offers an opportunity for social engagement and provides a culturally relevant purpose, environment, and space in which ole talk can take place. Ole talk is presented as a uniquely Caribbean way of engaging with one another in smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…As a very vital tool in African Oral traditional storytelling; a form of communal space to discuss issues within the community, and as a form of public education, fireside chat is apt for the story-gathering process in AOTS Framework. Like liming and ole talk in Caribbean research methodologies, fireside chat can extend beyond its communicative and social role to frame story gathering, sharing, and analysis (Nakhid-Chatoor et al, 2018; Santana et al, 2019) in the research process.…”
Section: Story Gathering In the Aots Framework: Fireside Chatmentioning
confidence: 99%
See 3 more Smart Citations
“…As a very vital tool in African Oral traditional storytelling; a form of communal space to discuss issues within the community, and as a form of public education, fireside chat is apt for the story-gathering process in AOTS Framework. Like liming and ole talk in Caribbean research methodologies, fireside chat can extend beyond its communicative and social role to frame story gathering, sharing, and analysis (Nakhid-Chatoor et al, 2018; Santana et al, 2019) in the research process.…”
Section: Story Gathering In the Aots Framework: Fireside Chatmentioning
confidence: 99%
“…The Fireside approach is therefore engendering a culturally centered redefinition of the relationship between the researcher/gatherer and the collaborators wherein knowledge is communal. This approach stands in contrast to the western-dominated paradigm wherein knowledge is treated as an item that can be found and owned by an individual (Nakhid-Chatoor et al, 2018; Wilson, 2008). Ntseane (2009) explicates how African researchers not only have to confront individualism in research but also research agenda, funding, writing, representation, and ways of engaging with collaborators.…”
Section: Story Gathering In the Aots Framework: Fireside Chatmentioning
confidence: 99%
See 2 more Smart Citations
“…For 28% of the respondents it is important to support other community members. Additionally, 10% of the respondents indicated that common achievements, sporting events and "liming", which can be described as a planned or spontaneous get-together for the purposes of relaxing, talking, or simply doing nothing is also important to the community [48]. Furthermore, fishing that was indicated by 18% and farming, mentioned by 10% of the respondents were considered to be important cultural activities.…”
Section: Integrationmentioning
confidence: 99%